Gender and multidimensional poverty in Nicaragua: An individual-based approach - José Espinoza-Delgado; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2017)
Most existing empirical papers concerned about multidimensional poverty use the house- hold as the unit of analysis, meaning that multidimensional poverty status of the household is equated with the multidimensional poverty status of all individuals in the household. This assumption, nonetheless, overlooks important within-household features and ignores the intra-household inequalities. Besides, by definition, households containing both a female and a male cannot contribute to a gender gap, so gender differentials cannot be estimated. But, the Sustainable Development Goals have put special emphasis on gender equality along their targets; therefore, new measures able to capture the gender differences are needed. Consequently, in this paper, we propose an individual-based multidimensional poverty mea- sure in order to estimate the three Is of multidimensional poverty (incidence, intensity, and inequality) in Nicaragua as well as the gender differentials. We also estimate logit regres- sions to better understanding the determinants of multidimensional poverty in this country. Overall, we find that there are statistically significant gender differences in multidimensional poverty in Nicaragua; but, they are estimated to be small and lower than 5%. However, the gender differential in inequality is larger than 10%, and it suggests that multidimensional poor women are living in very intense poverty when compared with multidimensional poor men. We also find that the elderly and children are the most vulnerable people in terms of multidimensional poverty in this country; furthermore, when information on employment, domestic work, and social protection is considered in the analysis, the gender gaps become more substantial, and women are more likely to be poor than men.
Keywords: I3; I32; D1; D13; D6; D63; O5; O54; 330; multidimensional poverty; poverty measurement; intra-household inequality; gender differences in poverty; Nicaragua; Latin America